Morphotectonic Control of Land Movements at Wundulako Region, Kolaka Regency, Southeast Sulawesi Province, Indonesia - Martono; Hasria; Suryawan Asfar; Muhammad Arba Azzaman; La Ode Ngkoimani; Ali Okto; La Hamimu; Irawati; Sawaludin; La Ode Muhammad Iradat Salihin; Wahab (Journal of Geoscience, Engineering, Environment, and Technology, 2022)
This research is located at Wundulako District, Kolaka Regency, Southeast Sulawesi Province. The purpose of this study are to determine the level of tectonic activity and the effect of tectonic activity on the land movement of the study area. Based on the DEM (Digital Elevation Model) analysis, geomorphology of the study area is dominated by mountains unit that indicate the influence of tectonic activity. Geomorphological aspects were analyzed to determine the tectonic classes in the study area such as watershed and non-watershed analysis. The results showed that, tectonic class of the study area is classified as very high and moderate tectonic class. The effect of tectonic class level on land movement in the study area shows a least correlation. This interprets that the cause of land movement at study area is not only influenced by tectonic factors but is also influenced by other factors such as rainfall, lithological conditions, geomorphology, earthquakes, and human activities. This shows that morphotectonic control has little effect on the land movements at Wundulako District, Kolaka Regency, Southeast Sulawesi Province, but is also influenced by other factors such as rainfall, lithological conditions, geomorphology, earthquakes, and human activities.